Tracing the provenance of volcanic ash in Permian–Triassic boundary strata, South China: Constraints from inherited and syn-depositional magmatic zircons - Zhao, T.; Algeo, T.; Feng, Q.; Zi, Jianwei; Xu, G. (Elsevier BV, 2019)
The Permian-Triassic boundary (PTB) mass extinction, the most severe biocrisis in Earth's history, is thought to have been triggered by catastrophic volcanic activity. PTB sections in South China contain numerous volcanic ash beds, the source of which is inferred to have been either the Siberian Traps Large Igneous Province (STLIP) or intraregional subduction-zone arc volcanism. In this study, the provenance of these ash beds is determined through a comprehensive analysis based on the geochronological and geochemical signatures of zircons from four PTB sections (Dongpan, Xinmin, Ganxi and Shangsi). Inherited zircons yielded U–Pb ages of 250–3521 Ma with major age clusters in the Permian, Carboniferous to Silurian, early Cambrian to Neoproterozoic, early Neoproterozoic to late Mesoproterozoic, and early Paleoproterozoic. The age spectrum of these zircons is similar to those of detrital zircons from sedimentary and magmatic rocks of the South China and Indochina cratons but different from those of the Siberian Craton, providing evidence for an intraregional source of the volcanic material. The trace-element, eHf(t), and d18O signatures of syn-depositional magmatic zircons are consistent with an arc-related/orogenic setting. PTB sections in South China can be assigned to sectors based on the number and cumulative thickness of ash beds and the length of zircon crystals. Sector I (South) includes the Dongpan and Xinmin sections, which have cumulative ash-bed thicknesses of 0.86–1.14 m and average zircon lengths of 151–217 µm. Sector II (North) includes the Ganxi, Shangsi and Daxiakou sections, which have cumulative ash-bed thicknesses of 0.17–0.33 m and average zircon lengths of 82–104 µm. Sector III (Northeast) includes the Niushan and Meishan sections, which have cumulative ash-bed thicknesses of 0.1–0.14 m and average zircon lengths of 71–73 µm. Systematic trends toward fewer and thinner ash beds and as well as smaller zircon sizes from Sector I to Sector III indicate a paleo-northward or -northeastward direction of ash transport. Collectively, our findings provide evidence that the source of volcanic ash in South China PTB sections was intraregional subduction-zone arc volcanism along the convergent margin between the South China and Indochina cratons.